Radiation risk perception among parents and legal representatives of children undergoing radiological examinations - A. M. Biblin; A. A. Davydov; A. V. Vodovatov; P. A. Strelnikova; A. N. Chernykh; V. G. Puzyrev (Радиационная гигиена)
Risk communication is one of the stages of health risk analysis and is an interactive process of exchange of information and opinions about risks, including medical risks, between risk assessment specialists, decision makers, the media, stakeholder groups and the public. In organizing interaction with stakeholders in the risk communication process, sociological research helps to explore the attitudes of the actors. One of risk communication situations in the field of radiation protection is information provision to patients and their legal representatives about radiation health risks due to the medical radiology examinations. The aim of this study was to assess the radiation risk perception among parents and legal representatives of children undergoing radiological examinations. Parents and legal representatives of children undergoing hospital treatment from November 2021 to March 2022 were interviewed in a large pediatric infectious diseases hospital. A questionnaire designed at St. Petersburg Research Institute of Radiation Hygiene was used for the interviews. In total, 125 people were interviewed. The study showed that there were no significant differences in the perception of radiation risks among parents and legal representatives of children undergoing inpatient treatment with different socio-demographic characteristics. The level of knowledge was not identified as a factor shaping a tolerant attitude toward medical radiation risks. Parents and legal representatives of children undergoing hospital treatment show high rates of trust in the attending physicians and medicine in general. The study results show that those who have been informed about the risks generally have lower risk perception for radiological medical examinations than those who have not been informed about the risks.